ANALISIS PERILAKU HARGA CPO (Crude Palm Oil) PADA PERUSAHAAN PT. PASANGKAYU SULAWESI BARAT - Fatimah, Fatimah; Hadayani, Hadayani; Kalaba, Yulianti (AGROTEKBIS, 2017)
The research objective ( Analysis the behavior of the price of palm oil CPO (Crude Palm Oil ) on PT. Pasangkayu company . The research was conducted on the Company PT.Pasangkayu December 2014- February 2015. The data analysis is simple regression and correlation analysis . The results of the analysis of price changes cpo in world prices by using simple regression analysis obtained my value = -1.02 + 1,22mx coefficient is real. this is indicated by thitung ( 19.89 ) > t table ( 3.012 ) with a value of 0.000 < 0.01 level of Î± = 1 % , that the changes in the world price for 1 exchange rate causes changes in the price of the company amounted to 1.22 rate level . correlation analysis is Y and X = 0.991 P -Value = 0.000 , analysis showed that changes in the level of the world price level cpo prices very influential company real .Â Key words : Price , CPO ,Â Correlation .